Pengaruh Teknologi Digital terhadap Perkembangan Bisnis Modern - Timoty Agustian Berutu; Dina Lorena Rea Sigalingging; Gaby Kasih Valentine Simanjuntak; Friska Siburian (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
In today's digital era, technology and information are developing very rapidly. The role of technology has brought benefits to humans in all aspects of the field, namely education, economics, social and culture, transportation, etc. With increasingly advanced technology, it is hoped that it will make human work easier in the future. Digital technology has changed the way we work, interact and do business. In today's digital era, old systems and processes must be rethought, and new technologies must be implemented so that businesses remain competitive and grow. High global competition places demands on business actors to continue to improve product innovation by utilizing existing technology to face this global challenge. Utilization of technology such as Increasing Operational Efficiency and Global Business can also help in understanding the changes that occur in the digital business ecosystem. The aim of this research is to determine the influence of digital technology on the development of modern business.